English A1 course companion - Druce, Elizabeth; Tyson, Hannah (New York : Oxford University Press, 2007)
A resource for students participating in the International Baccalaureate Diploma Programme that focuses on content and activities for English A1, which covers oral commentary, writing exam and extended essays, and more.
Includes index.
Young Adult
Keywords: English -- Study and teaching (Secondary); International baccalaureate; English -- Study and teaching; High schools -- Examinations; IB programme -- Language